SiO2-supported CeO2 as free radical scavengers

By adding cerium oxide-coated silica particles to the proton exchange membrane, the problem of hydrogen peroxide free radical erosion of the membrane was solved, the membrane stability and lifespan were improved, the preparation process was simplified, and the cost was reduced.

CN120936681APending Publication Date: 2025-11-11SOLVAY SPECIALTY POLYMERS ITALY SPA

Patent Information

Application Number
CN202380094254.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-12-19
Filing Date
2023-12-15
Publication Date
2025-11-11

AI Technical Summary

Technical Problem

In existing proton exchange membrane fuel cells and electrolyzers, hydrogen peroxide free radicals erode the membrane, leading to membrane degradation and affecting equipment lifespan. Existing methods suffer from insufficient stability or high costs.

Method used

The use of cerium oxide (CeO2) coated silica (SiO2) particles enhances the free radical degradation stability of the film by adding 10wt% to 70wt% Ce element to a fluorinated polymer with sulfonic acid functional groups, combined with high specific surface area and well-defined CeO2 crystallite size.

Benefits of technology

It improves the free radical degradation stability of proton exchange membranes, extends the service life of fuel cells and electrolyzers, and avoids the negative impact of sodium or potassium salts on membrane efficiency and stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005550184780000201
    Figure BDA0005550184780000201
  • Figure BDA0005550184780000301
    Figure BDA0005550184780000301
  • Figure BDA0005550184780000321
    Figure BDA0005550184780000321
Patent Text Reader

Abstract

Cerium oxide (CeO2) coated silica (SiO2) particles, optionally comprising the inorganic group-SO2X, and methods of making such particles. The addition of the cerium oxide (CeO2) coated silica (SiO2) particles to fluorinated polymers containing sulfonic acid functional groups increases their stability to free radical degradation when used in fuel cell applications or electrolytic applications.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] Citation of relevant applications

[0002] This application claims priority to European patent application EP22306930.3, filed on 19 December 2022, the entire contents of which are incorporated herein by reference for all purposes. Technical Field

[0003] This invention relates to cerium oxide (CeO2)-coated silica (SiO2) particles capable of improving the resistance of ion-exchange fluorinated polymer membranes to free radical degradation in fuel cell applications. The invention further relates to compositions comprising these cerium oxide-coated silica particles and ion-exchange fluorinated polymers, and ion-exchange membranes obtained therefrom. Finally, the invention relates to a method for preparing SiO2-supported CeO2. Background Technology

[0004] Fluorinated polymers containing sulfonic acid ion-exchange groups have found wide application in the manufacture of electrolyte membranes for electrochemical devices such as electrolyzers and fuel cells due to their ion-conducting properties. A notable example is, for instance, the proton exchange membrane (PEM) fuel cell, which uses hydrogen as fuel and oxygen or air as an oxidant.

[0005] In a typical PEM fuel cell, hydrogen is introduced into the anode section, where it reacts and separates into multiple protons and multiple electrons. The membrane transports these protons to the cathode section while allowing an electron flow through the external circuitry to the cathode section to provide electricity. Oxygen is introduced into the cathode section and reacts with these protons and electrons to form water and heat.

[0006] The membrane requires excellent ion conductivity, gas barrier properties (to avoid direct mixing of hydrogen and oxygen), mechanical strength, and chemical, electrochemical, and thermal stability under battery operating conditions. In particular, long-term membrane stability is a critical requirement: the lifespan target for stationary fuel cell applications is up to 40,000 hours of operation, while 20,000 hours is the requirement for automotive fuel cell applications.

[0007] Proton exchange membranes used in water electrolysis applications require similar properties. In fact, in an electrolytic cell, water is introduced and oxidized at the anode to O2 and H2. + H + It is further reduced to H2 at the cathode and then collected.

[0008] The erosion of proton exchange membranes by hydrogen peroxide radicals (OH, OOH) (which are generated during the operation of fuel cells or electrolyzers) is often described as one of the causes of membrane degradation. Radical degradation of the membrane leads to a reduction in the service life of the fuel cell or electrolyzer. It is generally believed that, among other mechanisms, hydrogen peroxide is formed due to the reaction between hydrogen and oxygen permeating through the membrane. The hydrogen peroxide then decomposes to form peroxy and hydroxyperoxy radicals; see, for example, SCHLICK, S. et al. Degradation of fuel cell membranes using ESR methods: ex situ and in situ experiments. Polymer Preprints. 2009, Vol. 50, No. 2, pp. 745-746. Direct formation of radicals is also considered possible.

[0009] Several attempts have been made to reduce the free radical degradation of fluorinated proton exchange membranes, for example by incorporating suitable metal salts or oxides into the membrane. The use of salts of different metals (including rare earth metals, Al, and Mn) to increase the stability of ion exchange membranes used in fuel cells is disclosed, among other things, in EP 1702378 A (BDFIP HOLDINGS LTD) 20 / 09 / 2006 and EP 1662595 A (Toyota Central Research & Development Co., Ltd.) 31 / 05 / 2006.

[0010] US20070213209 A (DuPont) disclosed on 13 / 09 / 2007 a formulation for decomposing hydrogen peroxide in a fuel cell membrane electrode assembly. This formulation comprises metal oxides from the group consisting of: alumina, silica, titanium dioxide, zirconium oxide, manganese dioxide, Y₂O₃, Fe₂O₃, FeO, tin oxide, copper oxide, nickel oxide, tungsten oxide, germanium oxide, and cerium oxide; a stabilizer selected from the group consisting of metal ions and metalloid ions (e.g., boron); and at least one catalyst different from the stabilizer and selected from the group consisting of cerium and ruthenium. The formulations disclosed in US20070213209 are prepared by adsorbing a catalyst onto a metal oxide pre-modified by a stabilizer. The catalyst particles are therefore not bound into the lattice of the metal oxide and may thus permeate into and subsequently efflux from the membrane during fuel cell operation.

[0011] ZHAO, D. et al. MnO2 / SiO2-SO3H nanocomposite as hydrogen peroxide scavenger for durability improvement in proton exchange membranes. J. Membrane Science. 2010, Vol. 346, pp. 143-151. This paper discloses nanoscale mixed MnO2 / SiO2 oxides with organic sulfonic acid groups grafted onto their surfaces. These blends are prepared by precipitating SiO2 onto the surface of nanoscale MnO2 and then reacting the surface hydroxyl groups of SiO2 with suitable organic sulfonating agents (such as cyclosulfonates). In the mixed MnO2 / SiO2 oxides disclosed by Zhao et al., MnO2 is physically bound only to SiO2, which may lead to the reduction of Mn(IV) to Mn(II) during fuel cell operation, and given the higher solubility of Mn(II) substances, their subsequent removal is also a concern.

[0012] GILL, CS et al. disclosed hybrid organic / inorganic catalysts containing organic sulfonic acids grafted onto a silica-coated magnetic nanoparticle support. J. Catalysis. 2007, Vol. 251, pp. 145-152.

[0013] In both systems described above, the organically hydrogenated portion immobilizes the –SO3H group onto the SiO2 surface. The presence of these hydrogenated organic portions in the inorganic oxide is considered to make the system unsuitable for use in fuel cells, as it could provide an additional source of free radical generation or degradation in the membrane under the highly oxidizing operating conditions of fuel cells.

[0014] WO 2014 / 009334 (Solvay Specialty Polymers Italy SpA) discloses that adding certain mixed oxides of Si and at least one metal M to fluorinated polymers containing sulfonic acid functional groups increases the stability of proton exchange membranes prepared therefrom against free radical degradation. However, the mixed oxides typically contain a Si / M weight ratio ranging from 1 to 40, corresponding to high to very high amounts of SiO2, and therefore contain very little Ce, the substance responsible for protecting against free radical degradation. Furthermore, the method disclosed therein includes a hot acid washing step, which increases safety concerns and costs.

[0015] US4360388 (Degussa Aktiengesellschaft) discloses cerium-containing precipitated silica and compositions of cerium-containing precipitated silica based on diorganopolysiloxanes that can be cured into elastomers. Cerium-containing precipitated silica is also disclosed as a flame retardant. The cerium-containing precipitated silica has a maximum thickness of 140 ± 40 μm as measured by BET according to DIN 66 131. 2 The specific surface area is given as / g; no description is given regarding the size of the cerium dioxide crystallites. The method disclosed in US4360388 involves aqueous solutions of cerium(IV), such as Ce(SO4)2,4H2O.

[0016] JP10230162 (Daikin Industries Ltd) discloses a silica-supported cerium dioxide catalyst, wherein the size of the cerium dioxide crystallites, as measured by half-width XRD, is no greater than 4 nm and the total specific surface area, as measured by nitrogen adsorption using BET, is greater than 200 m². 2 / g. There is no description of using such materials to enhance the stability of proton exchange membranes against free radical degradation. The method disclosed in JP10230162 is carried out at a pH value not exceeding 6.5 and involves the use of sodium hydroxide, sodium carbonate, or potassium hydroxide. The use of such bases may be the reason for the presence of sodium or potassium salts in the final product. Summary of the Invention

[0017] It has now been found that adding cerium oxide (CeO2)-coated silica (SiO2) particles to fluorinated polymers containing sulfonic acid functional groups increases the stability of proton exchange membranes prepared therefrom against free radical degradation, without the limitations of existing techniques. These cerium oxide (CeO2)-coated silica (SiO2) particles contain 10 wt% to 70 wt% Ce element relative to the total particle weight, exhibiting a range of 80 m / s as measured by BET. 2 / g to 220m 2The membrane has a specific surface area of ​​ / g and contains CeO2 microcrystals with dimensions ranging from 5.0 nm to 10.0 nm as measured by XRD. This increased stability is reflected in a longer service life when the membrane is used in fuel cells.

[0018] Regarding the prior art, it has been found that the high Ce content in cerium oxide (CeO2) coated silica (SiO2) particles according to the present invention, combined with a high specific surface area and well-defined cerium oxide crystallite size, provides improved stability against free radical degradation for proton exchange membranes prepared from fluorinated polymers containing sulfonic acid functional groups.

[0019] Therefore, the first object of the present invention is cerium oxide (CeO2) coated silicon dioxide (SiO2) particles containing 10 wt% to 70 wt% Ce element relative to the total particle weight, exhibiting a range of 80 μm as measured by the BET method. 2 / g to 220m 2 The specific surface area is / g, comprising CeO2 microcrystals with dimensions ranging from 5.0 nm to 10.0 nm as measured by XRD. The (CeO2) coated silica (SiO2) particles may optionally contain inorganic -SO2OZ functional groups, wherein Z is selected from the group consisting of H, alkali metals and NH4.

[0020] A second objective of the present invention is a liquid composition (LC1) comprising cerium oxide-coated silica particles dispersed in a liquid medium (L1) for the first objective.

[0021] A third objective of the present invention is a method A for preparing cerium oxide-coated silica particles for the first objective, the method comprising the following steps:

[0022] a) Provide an aqueous suspension (S1) containing SiO2, wherein the pH of the suspension is set between 7 and 11 by adding an aqueous ammonia (NH3) solution;

[0023] b) While maintaining the pH value between 7 and 11 by adding an aqueous ammonia solution, an aqueous Ce(NO3)3 solution is added to the suspension (S1) under stirring to obtain a slurry containing cerium hydroxide precipitated on SiO2.

[0024] c) Filter the slurry obtained in step b) to recover cerium hydroxide precipitated onto SiO2 in solid form;

[0025] d) The solid obtained in step c) is calcined in an oxidizing atmosphere at a temperature ranging from 250°C to 800°C for a duration ranging from 1 to 10 hours to obtain cerium oxide (CeO2) coated silicon dioxide (SiO2) in particulate form.

[0026] e) Optionally grind the recovered particles from step d) to obtain the desired particle size.

[0027] The fourth objective of this invention is a method A' for preparing cerium oxide-coated silica particles for the first objective, the method comprising the following steps:

[0028] a') Provide an ammonia solution (E) with a pH value set between 7 and 11;

[0029] b') While maintaining the pH value between 7 and 11 by adding an aqueous ammonia solution (E'), an aqueous suspension (S2) containing SiO2 suspended in an aqueous Ce(NO3)3 solution is added to the aqueous solution (E) under stirring to obtain a slurry containing cerium hydroxide precipitated on SiO2.

[0030] c') The slurry obtained in filtration step b') is used to recover cerium hydroxide precipitated onto SiO2 in solid form;

[0031] d') The solid obtained in step c') is calcined in an oxidizing atmosphere at a temperature ranging from 250°C to 800°C for a duration ranging from 1 to 10 hours to obtain cerium oxide (CeO2) coated silicon dioxide (SiO2) in particulate form.

[0032] e') Optionally, the recovered particles from step d') are milled to obtain the desired particle size.

[0033] The fifth objective of this invention is a method B for preparing cerium oxide (CeO2) coated silicon dioxide (SiO2) particles for the first objective, the method comprising the following steps:

[0034] a”) provides an aqueous suspension (S3) comprising SiO2, ammonia (NH3) and optionally at least one inorganic group -SO2OZ source;

[0035] b”) Add an amount of Ce(NO3)3 aqueous solution to the suspension (S3) under stirring, such that the molar ratio of NH3 to Ce provided in step a”) is in the range of 2 to 4, to obtain a slurry containing cerium hydroxide precipitated on SiO2.

[0036] c) Filter the slurry to recover cerium hydroxide Ce(OH)3, which has precipitated onto SiO2 in solid form;

[0037] d”) The obtained solid was calcined in an oxidizing atmosphere at a temperature ranging from 250°C to 800°C for a duration ranging from 1 to 10 h to obtain cerium oxide (CeO2) coated silicon dioxide (SiO2) in particulate form.

[0038] e”) optionally mill the recovered particles in step d”) to obtain the desired particle size.

[0039] As described in methods A, A', and B of this invention, the advantage of using ammonia instead of NaOH or KOH to set or adjust the pH is that there is no residual salt in the final product. In practice, when the cerium oxide-coated silica particles according to this invention are used in fuel cell applications, the presence of sodium or potassium salts can impair the efficiency and stability of the polymer membrane.

[0040] In fact, without being bound by any theory, if some ammonia is retained in the product before calcination after the corresponding steps c), c'), or c”), then this ammonia can be easily removed from the desired product during the calcination process carried out in the corresponding steps d), d'), or d”).

[0041] Therefore, the advantage of using ammonia to adjust the pH is that the salt does not need to be washed off before recovering the final product, thus simplifying the process.

[0042] Similarly, the advantage of using Ce(NO3)3 as a raw material is that if some of it is retained in the product before calcination after the corresponding steps c), (c'), or c”), it is converted into nitrogen oxides (NO3) during the calcination process in the corresponding steps d), d'), or d”). x (It is a gas and therefore easily removed from the desired product) and CeO2.

[0043] The sixth object of the present invention is a composition (C) comprising at least one fluorinated polymer containing a -SO2X functional group (wherein X is selected from X' or OZ and wherein X' is selected from the group consisting of F, Cl, Br, and I and Z is selected from the group consisting of H, alkali metals, and NH4) and particles of the first object.

[0044] Another object of the present invention is a liquid composition (LC) comprising composition (C).

[0045] Another objective is a method for preparing composition (C) or (LC).

[0046] Another object of the present invention is an article, particularly a membrane or electrocatalyst layer, comprising at least one fluorinated polymer containing a –SO2X functional group as defined above and cerium oxide (CeO2) coated silica (SiO2) particles.

[0047] Finally, another objective is a fuel cell or electrolyzer that includes articles according to the invention.

[0048] Disclosure of the invention

[0049] The first objective of this invention is cerium oxide (CeO2) coated silicon dioxide (SiO2) particles containing 10 wt% to 70 wt% Ce element relative to the total particle weight, exhibiting a range of 80 μm as measured by BET. 2 / g to 220m 2 The specific surface area is / g, comprising CeO2 microcrystals with dimensions ranging from 5.0nm to 10.0nm as measured by XRD.

[0050] Cerium oxide (CeO2) coated silica (SiO2) particles optionally contain inorganic -SO2OZ functional groups, wherein Z is selected from the group consisting of H, alkali metals, and NH4. The term "inorganic group -SO2OZ" as used herein with respect to cerium oxide (CeO2) coated silica (SiO2) particles indicates that the -SO2OZ group present in the cerium oxide coated silica particles is not combined with an organic portion, wherein the expression "organic portion" indicates any portion containing at least one carbon atom. All -SO2OZ groups in cerium oxide coated silica particles are inorganic -SO2OZ groups.

[0051] Unbound by theory, it is believed that the -SO2OZ group is bonded to the surface of cerium oxide-coated silica particles via sulfur atoms. The -SO2OZ group is bonded to at least one Si, Ce, or oxygen atom via sulfur atoms. Typically, the -SO2OZ group is bonded to at least a portion of metallic Ce via sulfur atoms.

[0052] The cerium oxide (CeO2) coated silica (SiO2) particles according to the present invention contain 10 wt% to 70 wt% Ce element relative to the total particle weight. In some embodiments, the cerium oxide coated silica particles contain 40 wt% to 70 wt%, or even 40 wt% to 65 wt% Ce element. In some other embodiments, the cerium oxide coated silica particles contain 50 wt% Ce element. In still some other embodiments, the cerium oxide coated silica particles contain 10 wt% to 45 wt%, or even 10 wt% to 40 wt% Ce element.

[0053] The theoretical Ce content is determined by using an appropriate amount of raw material before particle preparation. This content can be confirmed after synthesis by ICP-OES analysis of the cerium oxide-coated silica particles according to the present invention. Inductively coupled plasma optical emission spectrometry (ICP-OES) is performed on the mineralized samples prepared by methods well known to those skilled in the art.

[0054] When present, the amount of inorganic SO2OZ groups in cerium oxide-coated silica particles is typically at least 0.2% of the total atomic weight of Ce, and typically at least 0.5%. The amount of inorganic SO2OZ groups in cerium oxide-coated silica particles can be up to 50% relative to the total atomic weight of Ce. The inorganic SO2OZ groups can be bonded to Ce, Si, or oxygen atoms in cerium oxide (CeO2)-coated silica (SiO2) particles.

[0055] The amount of inorganic SO2OZ groups in cerium oxide-coated silica particles can be determined by ICP-OES measurement of S content, as is generally known to those skilled in the art.

[0056] Preferably, the cerium oxide-coated silica particles do not contain any organic portion as defined above, i.e., any portion containing at least one carbon atom.

[0057] The cerium oxide-coated silica particles according to the present invention exhibit a range of 80 μm as measured by BET. 2 / g to 220m 2 / g; typically the range is 100m 2 / g to 220m 2 / g; sometimes the range is 130m 2 / g to 220m 2 Specific surface area per g. In some cases, the specific surface area measured by BET may not exceed 215 m². 2 / g, or even no more than 210m 2 / g or even no more than 200m 2 / g.

[0058] The cerium oxide-coated silica particles according to the present invention have such that D 50 <0.20μm, preferably D 50 A particle size distribution of <0.18 μm was obtained by laser diffraction from a dispersion of particles in 1-propanol.

[0059] D 50 It has the usual meaning used in the field of particle size distribution. For clarity, D n Corresponding to the diameter of the particles, where the particles with a volume of n% have a diameter less than D. n The diameter of D. Therefore, D 50 The median is defined as the size value corresponding to the 50% cumulative distribution, which is a volume distribution.

[0060] Furthermore, the particles according to the invention typically have D 90 <0.50μm, preferably D 90 <0.45μm, more preferably D90 <0.42 μm, this distribution was obtained by laser diffraction from the dispersion of particles in 1-propanol.

[0061] In some embodiments, the cerium oxide-coated silica particles according to the present invention have D 50 <0.20μm and D 90 <0.50μm, both are based on volume.

[0062] The cerium oxide-coated silica particles according to the present invention comprise CeO2 microcrystals having dimensions ranging from 5.0 nm to 10.0 nm; 5.0 nm to 9.0 nm; 5.0 nm to 8.0 nm; and in some cases from 5.0 nm to 7.8 nm as measured by XRD.

[0063] Typically, cerium oxide microcrystals are formed on and thus bonded to silica particles.

[0064] It is believed that when used in proton exchange membranes in electrochemical devices, CeO2 microcrystals with smaller dimensions may cause problems with the leaching of Ce ions from the particles.

[0065] A second object of the present invention is a liquid composition (LC1) comprising cerium oxide-coated silica particles according to the present invention dispersed in a liquid medium (L1).

[0066] The cerium oxide-coated silica particles contained in (LC1) are typically characterized by D 50 <0.20μm, preferably D 50 <0.18μm.

[0067] Furthermore, the particles contained in (LC1) are typically characterized by D 90 <0.50μm, preferably D 90 <0.45μm, more preferably D 90 <0.42μm.

[0068] In some embodiments, the cerium oxide-coated silica particles included in (LC1) are characterized by the following particle size distribution: D 50 <0.20μm and D 90 <0.50μm.

[0069] In some embodiments, the liquid medium includes water, alcohol, or a water / alcohol mixture (L1).

[0070] Suitable alcohols that can be used (especially as water / alcohol mixtures) include methanol, ethanol, propanol (i.e., 1-propanol, 2-propanol), ethylene glycol, and diethylene glycol.

[0071] In some other embodiments, the liquid medium (L1) further comprises polar aprotic organic solvents such as ketones, like acetone, methyl ethyl ketone, esters, like methyl acetate, dimethyl carbonate, diethyl carbonate, ethyl acetate, nitriles, like acetonitrile, sulfoxides, like dimethyl sulfoxide (DMSO), sulfones, like dimethyl sulfone (DMSO2), amides, like N,N-dimethylformamide, N,N-dimethylacetamide, pyrrolidones, like N-methylpyrrolidone, N-ethylpyrrolidone, and mixtures thereof.

[0072] In some embodiments, the liquid medium (L1) is water, alcohol, or a mixture of water and alcohol, preferably a mixture of water and propanol.

[0073] Good results were obtained with a liquid composition (LC1) comprising particles according to the invention dispersed in 1-propanol, 2-propanol and mixtures thereof.

[0074] Typically, the liquid composition (LC1) according to the invention is prepared by suspending particles according to the invention in a liquid medium (L1) via stirring at room temperature.

[0075] In some embodiments, the liquid composition (LC1) is prepared by sonicating the particles according to the invention in a liquid medium (L1) for 0.5 h to 6 h to obtain a complete dispersion of the particles.

[0076] In some other embodiments, the liquid composition (LC1) is prepared by suspending particles according to the invention in a liquid medium (L1) by stirring at room temperature and by further sonication to obtain a complete dispersion of solids.

[0077] In some other embodiments, the liquid composition (LC1) is prepared by wet milling cerium oxide-coated silica particles according to the invention in a liquid medium (L1) to achieve a desired particle size distribution, and then suspending the particles in an additional amount (L1) as described above to achieve a desired content of cerium oxide-coated silica particles in wt% based on the total weight of the liquid composition (LC1).

[0078] The liquid composition (LC1) according to the invention typically contains at least 0.1 wt%, preferably at least 0.5 wt%, and more preferably at least 1.0 wt% of cerium oxide-coated silica particles based on the total weight of the liquid composition (LC1).

[0079] The liquid composition (LC1) according to the invention typically comprises up to 25.0 wt%, preferably up to 20.0 wt%, and more preferably up to 15.0 wt%, of cerium oxide-coated silica particles based on the total weight of the liquid composition (LC1).

[0080] Typically, the liquid composition (LC1) according to the invention comprises 0.1 wt% to 25.0 wt%, preferably 1.0 wt% to 15.0 wt% of cerium oxide-coated silica particles based on the total weight of the liquid composition (LC1).

[0081] In some embodiments, the liquid composition (LC1) according to the invention contains additional ingredients and / or additives, such as amines or carboxylic acids.

[0082] The cerium oxide (CeO2) coated silicon dioxide (SiO2) particles of the present invention can be prepared by method A, which includes the following steps:

[0083] a) Provide an aqueous suspension (S1) containing SiO2, wherein the pH of the suspension is set between 7 and 11 by adding an aqueous ammonia (NH3) solution;

[0084] b) While maintaining the pH between 7 and 11 by adding an aqueous ammonia solution, an aqueous Ce(NO3)3 solution is added to the suspension (S1) under stirring to obtain a slurry containing cerium hydroxide precipitated onto SiO2.

[0085] c) Filter the slurry obtained in step b) to recover cerium hydroxide precipitated onto SiO2 in solid form;

[0086] d) The solid obtained in step c) is calcined in an oxidizing atmosphere at a temperature ranging from 250°C to 800°C for a duration ranging from 1 to 10 hours to obtain cerium oxide (CeO2) coated silicon dioxide (SiO2) in particulate form.

[0087] e) Optionally grind the recovered particles from step d) to obtain the desired particle size.

[0088] Method A is typically performed when the target cerium oxide-coated silica particles contain 10 wt% to 70 wt% Ce element.

[0089] In some preferred embodiments, method A is performed when the target cerium oxide-coated silica particles contain more than 40 wt% and up to 70 wt% Ce element.

[0090] In step a) of the method, the aqueous suspension (S1) typically contains 5 wt% to 10 wt% SiO2 relative to the total weight of the aqueous suspension (S1). Preferably, the aqueous suspension (S1) contains 5 wt% to 8 wt%, more preferably 6 wt% to 7 wt% SiO2 relative to the total weight of the aqueous suspension (S1). Good results were obtained with a suspension (S1) containing 6.5 wt% SiO2.

[0091] The aqueous ammonia (NH3) solution used in steps a) and b) of this method typically contains 5 wt% to 11 wt% ammonia. Preferably, it contains 6 wt% to 10 wt%, more preferably 7 wt% to 9 wt% ammonia. Good results were obtained with an aqueous solution containing 8 wt% ammonia.

[0092] Typically, in steps a) and b), the pH is set and maintained between 7 and 11 by adding an aqueous ammonia solution. Good results were obtained while setting and maintaining the pH at 8.5.

[0093] In some embodiments, in step a), the pH is set to a value between 7 and 11, which is different from the pH value between 7 and 11 maintained in step b).

[0094] In step b), the concentration of the Ce(NO3)3 aqueous solution added to the suspension (S1) typically ranges from 1.00 mol / L to 5.00 mol / L, preferably from 1.50 mol / L to 4.00 mol / L. Good results were obtained with a concentration of 2.87 mol / L.

[0095] Ce(NO3)3 solution is typically added to the suspension (S1) while stirring for 10 minutes to 3 hours; preferably, the time period is 30 minutes to 2 hours. A one-hour duration yielded good results.

[0096] In step c), filtration can be performed on a laboratory scale using, for example, a Buchner funnel. On a larger scale, any filtration system known in the art for dewatering, such as a filter press, can be used.

[0097] In step d), calcination can be carried out in any oven under an oxidizing atmosphere. For example, calcination can be carried out in a rotary kiln. In some embodiments, air is the oxidizing atmosphere.

[0098] Typically, calcination is carried out at temperatures ranging from 250°C to 800°C, preferably from 400°C to 800°C. Calcination at 500°C yielded good results.

[0099] In some embodiments, calcination is carried out at 800°C.

[0100] Typically, the calcination duration ranges from 1 to 10 hours, preferably from 2 to 8 hours. Good results were obtained with calcination performed at 500°C for 3 hours. In some embodiments, calcination was performed at 800°C for 3 hours.

[0101] In step e), grinding can be performed by processing the particles obtained in step d) in any equipment familiar to a technician, such as a hammer mill, planetary ball mill, knife mill, or jet mill.

[0102] In some embodiments, milling can be carried out in the presence of at least one solvent, i.e., via so-called wet milling using suitable, well-known instruments. Suitable solvents for wet milling are 1-propanol, 2-propanol, ethanol, water, and mixtures thereof. Good results have been obtained using 1-propanol or 2-propanol.

[0103] In some other embodiments, dry milling is performed beforehand, followed typically by wet milling using 1-propanol.

[0104] Typically, in step e), cerium oxide (CeO2) coated silicon dioxide (SiO2) particles are deagglomerated by dry grinding.

[0105] In order to achieve the presentation of D 50 <0.20μm and D 90 Cerium oxide-coated silica particles <0.50 μm are typically wet-milled in step e).

[0106] In some embodiments, in order to obtain the presentation of D 50 <0.20μm and D 90 In step e), cerium oxide-coated silica particles with a diameter of <0.50 μm are dry-milled before wet milling.

[0107] In other embodiments, the cerium oxide (CeO2) coated silicon dioxide (SiO2) particles of the present invention can be prepared by method A', which includes the following steps:

[0108] a') Provide an ammonia solution (E) with a pH value set between 7 and 11;

[0109] b') While maintaining the pH value between 7 and 11 by adding an aqueous ammonia solution (E'), an aqueous suspension (S2) containing SiO2 suspended in an aqueous Ce(NO3)3 solution is added to the solution (E) under stirring to obtain a slurry containing cerium hydroxide precipitated on SiO2.

[0110] c') The slurry obtained in step b') is used to recover cerium hydroxide precipitated onto SiO2 in solid form;

[0111] d') The solid obtained in step c') is calcined in an oxidizing atmosphere at a temperature ranging from 250°C to 800°C for a duration ranging from 1 to 10 hours to obtain cerium oxide (CeO2) coated silicon dioxide (SiO2) in particulate form.

[0112] e') Optionally, the recovered particles from step d') are milled to obtain the desired particle size.

[0113] Typically, method A' is performed when the target cerium oxide-coated silica particles contain 10 wt% to 70 wt% Ce element.

[0114] In some preferred embodiments, method A' is performed when the target cerium oxide-coated silica particles contain more than 40 wt% and up to 70 wt% Ce element.

[0115] The aqueous ammonia (NH3) solution (E) used in step a') of method A' typically contains 5 wt% to 11 wt% ammonia. Sometimes it contains 6 wt% to 10 wt%, and often 7 wt% to 9 wt% ammonia.

[0116] The aqueous ammonia (NH3) solution (E') used in step b' of method A' typically contains 5 wt% to 11 wt% ammonia. Sometimes it contains 6 wt% to 10 wt%, and often 7 wt% to 9 wt% ammonia.

[0117] In some embodiments, the ammonia (NH3) aqueous solution (E) is different from (E').

[0118] In some embodiments, the ammonia (NH3) aqueous solution (E) is the same as (E').

[0119] Typically, in steps a') and b'), the pH is set and maintained between 7 and 11 by adding ammonia solution. Sometimes the pH is set and maintained at 8.5.

[0120] In some embodiments, in step a'), the pH is set to a value between 7 and 11, which is different from the pH value maintained between 7 and 11 in step b').

[0121] In step b'), the concentration of the Ce(NO3)3 aqueous solution typically ranges from 1 mol / L to 5 mol / L, and sometimes from 1.5 mol / L to 4 mol / L.

[0122] In step b') of the method, the aqueous suspension (S2) typically contains 2.5 wt% to 15.0 wt% of SiO2 relative to the total weight of the aqueous suspension (S2).

[0123] In step b'), the aqueous suspension (S2) typically contains 2.5 wt% to 15.0 wt% SiO2 dispersed in an aqueous solution of 1 mol / L to 5 mol / L Ce(NO3)3 relative to the total weight of the aqueous suspension (S2).

[0124] The suspension (S2) is usually added to the solution (E) while stirring for 10 minutes to 3 hours; sometimes for 30 minutes to 2 hours; and often for one hour.

[0125] Steps c'), d') and e') are generally performed as previously described for steps c), d), and e).

[0126] In other embodiments, the cerium oxide (CeO2) coated silicon dioxide (SiO2) particles of the present invention are prepared by method B, which includes the following steps:

[0127] a”) provides an aqueous suspension (S3) comprising SiO2, ammonia (NH3) and optionally at least one inorganic group –SO2OZ source;

[0128] b”) Add an amount of Ce(NO3)3 solution to the suspension (S3) under stirring, such that the molar ratio of NH3 to Ce provided in step a”) is in the range of 2 to 4, to obtain a slurry containing cerium hydroxide precipitated on SiO2.

[0129] c”) Filter the slurry to recover cerium hydroxide Ce(OH)3, which is precipitated onto SiO2 in solid form;

[0130] d”) The obtained solid is calcined in an oxidizing atmosphere at a temperature ranging from 250°C to 800°C for a duration ranging from 1 to 10 hours to obtain cerium oxide-coated silica in particulate form.

[0131] e”) optionally mill the recovered particles in step d”) to obtain the desired particle size.

[0132] Method B is typically performed when the target cerium oxide (CeO2) coated silica (SiO2) particles contain 10 wt% to 40 wt% Ce element.

[0133] In step a) of this method, the aqueous suspension (S3) typically contains 4 wt% to 10 wt% SiO2 relative to the total weight of the aqueous suspension (S3). The aqueous suspension (S3) preferably contains 4.5 wt% to 8 wt%, more preferably 5 wt% to 7 wt% SiO2 relative to the total weight of the aqueous suspension (S3). Good results were obtained with a suspension containing 6.5 wt% SiO2.

[0134] In step b), the concentration of the Ce(NO3)3 solution added to the suspension (S3) is typically in the range of 1 mol / L to 5 mol / L, preferably 1.5 mol / L to 4 mol / L. Good results were obtained with a concentration of 2.87 mol / L.

[0135] In step b), the Ce(NO3)3 solution is typically added in an amount such that the molar ratio of NH3 to Ce provided in step a) ranges from 2.0 to 4.0, typically from 2.5 to 3.5. Adding the Ce(NO3)3 solution in an amount such that the molar ratio of NH3 to Ce provided in step a) is equal to 3.0 yielded good results.

[0136] Ce(NO3)3 solution is typically added to the suspension (S3) while stirring for 15 minutes to 3 hours; preferably, the timeframe is 30 minutes to 2 hours. Good results were obtained when Ce(NO3)3 solution was added to the suspension (S3) for one hour.

[0137] Steps c”), d”) and e”) are generally performed as previously described for steps c), d) and e).

[0138] In some embodiments, step a) of method B includes providing an aqueous suspension containing SiO2, ammonia (NH3) and at least one inorganic group – SO2OZ source.

[0139] Suitable inorganic group –SO2OZ sources are, for example, those selected from the group consisting of (NH4)2SO3·H2O, NH4SO3NH2, HSO3Cl, Na2S2O5 / NaHSO3, (NH4)HSO3, and H2SO4. Preferably, the inorganic group –SO2X source is (NH4)2SO3·H2O.

[0140] When present, the inorganic group –SO2OZ source is typically 2 wt% to 10 wt%, preferably 5 wt% to 7 wt%, of the total amount of SiO2 and Ce(NO3)3 added throughout the process of Method B.

[0141] In some embodiments, the aqueous suspension (S1), (S2), or (S3) of the corresponding method A, A', or B may contain a polar solvent, such as an alcohol.

[0142] Typically, in the processes of methods A, A' and B according to the invention, cerium oxide microcrystals are formed on and thus bonded to silicon dioxide particles.

[0143] In some embodiments, the cerium oxide-coated silica particles according to the present invention are substantially free of free cerium oxide microcrystals not connected to the silica particles.

[0144] In some other embodiments, the cerium oxide-coated silica particles according to the present invention are completely free of free cerium oxide microcrystals not connected to the silica particles.

[0145] Any type of silica (SiO2) can be used to prepare cerium oxide (CeO2) coated silica (SiO2) particles according to the present invention, such as colloidal silica, fumed silica, precipitated silica, etc. Preferably, SiO2 having a particle size of 1.0 nm to 100.0 nm, more preferably 5.0 nm to 50.0 nm, is preferred.

[0146] Notable, non-limiting examples of suitable commercially available precipitated silica are, for example: 73. 63. SoftClean 43. 331, all available from Solvay SA.

[0147] Colloidal silica, available from WR Grace & Co., can also be used.

[0148] Ce(NO3)3·6H2O is commonly used to prepare aqueous solutions of Ce(NO3)3.

[0149] Another object of the present invention is a composition (C) comprising at least one polymer containing a -SO2X functional group (wherein X is selected from X' or OZ and wherein X' is selected from the group consisting of F, Cl, Br, I and Z is selected from the group consisting of H, alkali metals, NH4) and cerium oxide (CeO2) coated silicon dioxide (SiO2) particles as detailed above.

[0150] Composition (C) may comprise at least one fluorinated polymer containing a –SO2X functional group (where X is selected from X' or OZ and X' is selected from the group consisting of F, Cl, Br, and I and Z is selected from the group consisting of H, alkali metals, and NH4) and cerium oxide (CeO2) coated silica (SiO2) particles as detailed above.

[0151] The term "fluorinated" is used herein to refer to compounds (e.g., compounds, polymers, monomers, etc.) that are completely or partially fluorinated (i.e., in which all or only some of the hydrogen atoms have been replaced by fluorine atoms). Preferably, the term "fluorinated" refers to a compound containing a higher proportion of fluorine atoms than hydrogen atoms, and more preferably, the term refers to a compound that contains no hydrogen atoms at all, i.e., in which all hydrogen atoms have been replaced by fluorine atoms.

[0152] In the context of this invention, the expression "at least one" when referring to "fluorinated polymer" is intended to indicate one or more polymers. Mixtures of polymers can be advantageously used for the purposes of this invention.

[0153] Composition (C) may comprise at least one fluorinated polymer in a neutral form, wherein the expression "neutral form" indicates that X is X' in the -SO2X functional group and X' is selected from the group consisting of F, Cl, Br, and I. Preferably, X' is selected from F or Cl. More preferably, X' is F.

[0154] Alternatively, composition (C) may comprise at least one fluorinated polymer in ionic (acidic or salt-forming) form, wherein the expression "ionic form" indicates that X is OZ in the -SO2X functional group and Z is selected from the group consisting of H, alkali metals, and NH4.

[0155] For the avoidance of ambiguity, the term "alkali metal" is hereby intended to refer to the following metals: Li, Na, K, Rb, Cs. Preferably, the alkali metal is selected from Li, Na, and K.

[0156] Fluorinated polymers containing the –SO3Z functional group (where X = OZ) are typically prepared by methods known in the art from fluorinated polymers containing the –SO2X' functional group, preferably the –SO2F functional group.

[0157] The fluorinated polymer can be obtained by treating the corresponding polymer containing the –SO2X' functional group, typically the –SO2F functional group, with a strong base (e.g., NaOH, KOH), in the form of its salt, i.e., where Z is a cation selected from the group consisting of NH4 and alkali metals.

[0158] The fluorinated polymer can be obtained in its acid form, i.e., where Z is H, by treating the salt form of the corresponding polymer with a concentrated acid solution.

[0159] Suitable fluorinated polymers containing –SO2X' functional groups are those polymers comprising repeating units derived from at least one olefinic unsaturated fluorinated monomer (as defined below, monomer (A)) containing at least one –SO2X' functional group and repeating units derived from at least one olefinic unsaturated fluorinated monomer (as defined below, monomer (B)).

[0160] Regarding monomers of types (A) and (B), the phrase "at least one monomer" is used herein to indicate that one or more monomers of each type may be present in the polymer. In the following text, the term monomer will be used to refer to both one and more monomers of a given type.

[0161] A suitable, non-limiting example of monomer (A) is:

[0162] - Sulfonyl fluoroalkenes with the following formula: CF2=CF(CF2) p SO2X', where p is an integer between 0 and 10, preferably between 1 and 6, more preferably p equals 2 or 3, and wherein preferably X' = F;

[0163] - Sulfonyl fluorovinyl ethers having the following formula: CF2=CF-O-(CF2) m SO2X', where m is an integer between 1 and 10, preferably between 1 and 6, more preferably between 2 and 4, and even more preferably m equals 2, and where preferably X' = F;

[0164] - Sulfonyl halogenated fluoroallylic ethers having the following formula: CF2=CFCF2-O-(CF2) q SO2X', where q is an integer between 1 and 10, preferably between 1 and 6, more preferably between 2 and 4, even more preferably q equals 2, and where preferably X' = F;

[0165] -Sulfonyl halofluoroalkoxy vinyl ethers having the following formula:

[0166] CF2 = CF - (OCF2CF(R) F1 )) w -O-CF2(CF(R F2 )) y SO2X'

[0167] Where w is an integer between 0 and 2, and R F1 and R F2 They may be the same as or different from each other, and are independently F, Cl, or C optionally substituted with one or more ether oxygens. 1- C 10 fluoroalkyl, y is an integer between 0 and 6; preferably, w is 1, R F1 It is -CF3, y is 1 and R F2 It is F, and preferably X' = F;

[0168] -Sulfonyl halide aromatic fluoroolefins having the formula CF2=CF-Ar-SO2X'

[0169] Where Ar is C 5- C 15 Aromatic or heteroaromatic substituents, wherein preferably X' = F.

[0170] Preferably, the monomer (A) is selected from the group consisting of sulfonyl fluorides, i.e., X' = F.

[0171] More preferably, monomer (A) is selected from those having the formula CF2=CF-O-(CF2). m -SO2F is a group of fluorovinyl ethers, wherein m is an integer between 1 and 6, preferably between 2 and 4.

[0172] Even more preferably, the monomer (A) is CF2=CFOCF2CF2-SO2F (perfluoro-5-sulfonyl fluoride-3-oxa-1-pentene).

[0173] Suitable (B) type olefinic unsaturated fluorinated monomers are:

[0174] -C2-C8 fluoroolefins, such as tetrafluoroethylene, pentafluoropropylene, hexafluoropropylene, and hexafluoroisobutylene;

[0175] - Vinylidene fluoride;

[0176] -C2-C8 chloro- and / or bromo- and / or iodo-fluoroolefins, such as chlorotrifluoroethylene and bromotrifluoroethylene;

[0177] -With the formula CF2 = CFOR f1 Fluoroalkyl vinyl ethers, wherein R f1 It is a C1-C6 fluoroalkyl group, such as -CF3, -C2F5, -C3F7;

[0178] -With the formula CF2 = CFOR O1 Fluoro-oxyalkyl vinyl ethers, wherein R O1 It is a C1-C having one or more ether groups. 12 Fluoroalkyl groups, such as perfluoro-2-propoxy-propyl;

[0179] -With the formula CF2=CFOCF2OR f2 Fluoroalkyl-methoxy-vinyl ethers, wherein R f2 It is a C1-C6 fluoroalkyl group, such as -CF3, -C2F5, -C3F7, or a C1-C6 fluorooxyalkyl group having one or more ether groups, such as -C2F5-O-CF3;

[0180] - Fluorodioxanes having the following formula:

[0181]

[0182] Where R f3 R f4 R f5 R f6 Each of them may be the same as or different from each other, and is independently a C1-C6 fluoroalkyl group containing one or more oxygen atoms, such as -CF3, -C2F5, -C3F7, -OCF3, -OCF2CF2OCF3.

[0183] Preferably, monomer (B) is selected from:

[0184] -C3-C8 fluoroolefins, preferably tetrafluoroethylene and / or hexafluoropropylene;

[0185] -Chloro- and / or brominated- and / or iodo-C2-C6 fluoroolefins, such as chlorotrifluoroethylene and / or brominatedtrifluoroethylene;

[0186] -With the formula CF2 = CFOR f1 Fluoroalkyl vinyl ethers, wherein R f1 It is a C1-C6 fluoroalkyl group, such as -CF3, -C2F5, -C3F7;

[0187] -With the formula CF2 = CFOR O1 Fluoro-alkoxy vinyl ethers, of which R O1 It is a C1-C having one or more ether groups. 12 Fluoroalkyl groups, such as perfluoro-2-propoxy-propyl.

[0188] More preferably, monomer (B) is tetrafluoroethylene.

[0189] Fluorinated polymers containing the –SO2X' functional group can be prepared by any polymerization method known in the art. Suitable methods for preparing such polymers are, for example, those described in EP 1323751A (SolvaySOLEXIS SPA) 02 / 07 / 2003 and EP 1172382 A (SolvaySOLEXIS SPA) 16 / 11 / 2002.

[0190] Alternatively, the polymer containing the –SO2X functional group can be a non-fluorinated polymer. This polymer can be an aromatic polymer.

[0191] Typical examples of aromatic polymers containing the –SO2X functional group suitable for composition (C) include polymers in which sulfonic acid groups are introduced into polymers having an aromatic ring in the main chain.

[0192] Polymers with aromatic rings in their main chain can have the main chain interrupted, for example, by heteroatoms such as oxygen atoms. Examples of such aromatic polymers include polyetherketones, polyetheretherketones, polysulfones, polyethersulfones, polyetherethersulfones, poly(arylene ethers), polyimides, polyphenylene, poly((4-phenoxybenzoyl)-1,4-phenylene), polyphenylene sulfide, and sulfonated aryl polybenzimidazoles, sulfonated alkylated polybenzimidazoles, phosphate-alkylated polybenzimidazoles, and phosphonate-esterified poly(phenylene ethers).

[0193] The cerium oxide (CeO2) coated silica (SiO2) particles according to the invention are present in composition (C) in any amount sufficient to reduce the free radical degradation of polymers containing –SO2X functional groups.

[0194] The amount of Ce element is typically at least 0.1 wt%, preferably at least 0.2 wt%, and more preferably at least 0.5 wt%, relative to the total weight of the polymer in the composition (C) containing cerium oxide (CeO2) coated silica (SiO2) particles according to the invention.

[0195] The amount of Ce element is generally no more than 20.0 wt%, preferably no more than 15.0 wt%, and more preferably no more than 10.0 wt%, relative to the total weight of the polymer in the composition (C) containing cerium oxide (CeO2) coated silica (SiO2) particles according to the invention.

[0196] The polymer containing the –SO2X functional group in composition (C) is preferably a fluorinated polymer.

[0197] Composition (C) can be prepared using conventional methods.

[0198] When both the fluorinated polymer and the cerium oxide (CeO2) coated silica (SiO2) particles are provided in solid form, such as as powder, granules or pellets, the composition (C) can be prepared using techniques such as dry blending, melt blending or extrusion.

[0199] Therefore, the object of the present invention is a method for preparing a composition (C) comprising blending, in solid form, cerium oxide (CeO2) coated silica (SiO2) of the present invention with at least one fluorinated polymer containing a –SO2X functional group.

[0200] Alternatively, another object of the present invention is a method for preparing a composition (C) comprising blending cerium oxide (CeO2) coated silica (SiO2) of the present invention with at least one fluorinated polymer containing a –SO2X functional group in a liquid medium (L) to provide a liquid composition (LC).

[0201] These methods are advantageous for preparing compositions (C) in which the fluorinated polymer contains -SO3Z functional groups (where Z is as defined above), and in particular -SO3H functional groups.

[0202] The liquid composition (LC2) can be prepared by a dissolution method, wherein the fluorinated polymer is contacted with the liquid medium (L2) under suitable temperature conditions.

[0203] Typically, the liquid medium (L2) contains water, alcohol, or a water / alcohol mixture, and optionally contains additional components and / or additives.

[0204] Suitable alcohols that can be used, especially as water / alcohol mixtures, include methanol, ethanol, propanol (i.e., isopropanol, n-propanol), ethylene glycol, and diethylene glycol.

[0205] The liquid medium (L2) may further comprise solvents selected from the following: polar aprotic organic solvents, such as ketones, like acetone, methyl ethyl ketone; esters, such as methyl acetate, dimethyl carbonate, diethyl carbonate, ethyl acetate; nitriles, such as acetonitrile; sulfoxides, such as dimethyl sulfoxide (DMSO); sulfones, such as dimethyl sulfone (DMSO2); amides, such as N,N-dimethylformamide, N,N-dimethylacetamide; pyrrolidones, such as N-methylpyrrolidone, N-ethylpyrrolidone; and mixtures thereof.

[0206] In some embodiments, the liquid medium (L2) comprises water or a mixture of water and alcohol, preferably a mixture of water and propanol.

[0207] Good results were obtained when the liquid medium (L2) was water or a mixture of water and alcohol, preferably a mixture of water and propanol.

[0208] Good results were also obtained when the liquid medium (L2) was a mixture of water, propanol and DMSO2.

[0209] The liquid composition (LC2) can be advantageously prepared by contacting the fluorinated polymer with water or a mixture of water and alcohol in an autoclave at room temperature or at a temperature of 40°C to 300°C.

[0210] In some other embodiments, the liquid composition (LC2) can be advantageously prepared by contacting the fluorinated polymer with water, propanol and DMSO2 in an autoclave at room temperature or at a temperature of 40°C to 300°C.

[0211] Pure cerium oxide (CeO2) coated silica (SiO2) particles or as the previously described liquid composition according to the invention (LC1) can be added to a liquid composition (LC2) containing a fluorinated polymer to obtain a liquid composition (LC) containing at least one fluorinated polymer containing a –SO2X functional group dispersed or dissolved in a liquid medium (L) and cerium oxide (CeO2) coated cerium dioxide (SiO2) particles.

[0212] Therefore, when pure cerium oxide (CeO2) coated silica (SiO2) particles are added, the liquid medium (L) is the liquid medium (L2), and when cerium oxide (CeO2) coated silica (SiO2) particles are added as a liquid composition (LC1), the liquid medium (L) is a combination of the liquid medium (L2) and the liquid medium (L1).

[0213] Another object of the present invention is a liquid composition (LC) comprising at least one fluorinated polymer containing a –SO2X functional group and cerium oxide (CeO2) coated silica (SiO2) particles dispersed or dissolved in a liquid medium (L) as previously described. Typically, the liquid medium (L) comprises water or a mixture of water and alcohol.

[0214] In some embodiments, the liquid medium (L) is water or a mixture of water and propanol, preferably 1-propanol.

[0215] In some other embodiments, the liquid medium (L) is a mixture of water, propanol (preferably 1-propanol), and DMSO2.

[0216] Preferably, the fluorinated polymer in the liquid composition (LC) is in its ionic form, i.e., it contains a -SO3Z functional group, where Z is as defined above, and in particular a -SO3H functional group.

[0217] A liquid composition (LC) comprising at least one fluorinated polymer and cerium oxide (CeO2) coated silica (SiO2) particles may optionally contain additional components.

[0218] Therefore, the object of the present invention is a method for preparing a liquid composition (LC) comprising blending cerium oxide (CeO2) coated silica (SiO2) particles and at least one fluorinated polymer containing a –SO2X functional group in a liquid medium (L).

[0219] The composition (C) of this invention is particularly suitable for preparing proton exchange membranes and electrocatalytic layers for fuel cell applications. It is also particularly suitable for preparing proton exchange membranes and electrocatalytic layers for water electrolysis applications. In fact, the presence of cerium oxide (CeO2) coated silica (SiO2) particles of this invention has been shown to improve the resistance of fluorinated polymers containing –SO2X functional groups to free radical degradation, as demonstrated by the longer lifetime of the proton exchange membranes obtained therefrom under operating conditions.

[0220] As previously mentioned, in the processes of methods A, A', and B according to the invention, cerium oxide microcrystals are formed on and thus bonded to the silica particles. Therefore, the cerium oxide scavenger can be immobilized within the membrane, thereby preventing dissolution during operation in the fuel cell or electrolyzer. In other words, cerium oxide is more stable against leaching during operation in the fuel cell or electrolyzer. Therefore, due to the presence of more cerium oxide, the fluorinated membrane is protected from free radical-induced degradation for a longer period. Furthermore, electrocatalyst poisoning and a shortened expected membrane lifetime due to dissolved cerium oxide are avoided.

[0221] The assessment of cerium oxide leaching can be performed, for example, by subjecting a membrane containing cerium oxide (CeO2)-coated silica (SiO2) particles of the present invention to a sulfuric acid solution. The amount of cerium oxide dissolved in the sulfuric acid during the membrane treatment can then be assessed by ICP-OES. Generally, leaching of cerium oxide from a membrane containing cerium oxide (CeO2)-coated silica (SiO2) particles of the present invention is reduced compared to leaching from membranes containing other cerium sources.

[0222] Another object of the present invention is an article comprising at least one fluorinated polymer containing a –SO2X functional group as defined above and cerium oxide (CeO2) coated silicon dioxide (SiO2) particles.

[0223] In the first embodiment, the article is a proton exchange membrane for fuel cell applications, also referred to herein as a "membrane".

[0224] A composition (C) comprising at least one fluorinated polymer (typically containing –SO2X' functional group, preferably –SO2F functional group) and cerium oxide (CeO2) coated silica (SiO2) particles in solid form can be advantageously converted into a film by conventional extrusion techniques.

[0225] The extruded membrane can then be converted into an ion-conducting membrane by hydrolysis, i.e., the –SO2X' functional group is converted into the corresponding -SO3H functional group, as discussed above.

[0226] The film can be obtained from the liquid composition (LC) according to the invention using techniques known in the art, such as impregnation, casting, coating (e.g., roll coating, gravure coating, reverse roll coating, dip coating, spray coating), the liquid composition comprising at least one fluorinated polymer and cerium oxide (CeO2) coated silica (SiO2) particles, the fluorinated polymer typically containing -SO3Z functional groups, preferably -SO3H functional groups.

[0227] These membranes can optionally be reinforced, for example, by laminating an extruded membrane onto a suitable reinforcing support or by impregnating a liquid composition (LC) onto a porous support. Suitable supports can be made from a wide variety of components. These porous supports can be made from hydrocarbon polymers (such as woven or nonwoven polyolefin membranes, e.g., polyethylene or polypropylene) or polyesters (e.g., polyethylene terephthalate). Fluorinated polymer porous supports are generally preferred for fuel cell applications due to their high chemical inertness. Biaxially expanded PTFE porous supports (also known as ePTFE membranes) are among the preferred supports. These supports are notably known by trade name. Available for commercial purchase.

[0228] In the second embodiment, the product is an electrocatalytic layer.

[0229] The electrocatalytic layer can advantageously be prepared from a liquid composition (LC) according to the invention, which comprises catalyst particles in addition to at least one fluorinated polymer and cerium oxide (CeO2)-coated silica (SiO2) particles, the fluorinated polymer typically containing –SO3Z functional groups, preferably –SO3H functional groups. The liquid composition is commonly referred to as “catalytic ink”. Typical catalyst particles comprise active compounds selected from metals such as iron, manganese, cobalt, nickel, platinum, ruthenium, gold, palladium, rhodium, and iridium; their conductive oxides and alloys. The active compound is typically supported on a suitable material (referred to herein as a “support”), which is preferably conductive. The support is advantageously selected from carbon powders, such as carbon black.

[0230] The amount of catalyst particles (including the support, if present) in the catalytic ink is typically at least 1 wt% based on the total weight of the catalytic ink. Preferably, it is at least 3 wt%, and more preferably at least 5 wt%. The amount of catalyst particles (including the support, if present) in the catalytic ink is advantageously at most 50 wt%, preferably at most 40 wt%, and more preferably at most 30 wt%, based on the total weight of the catalytic ink.

[0231] These electrocatalytic layers can be prepared, for example, by screen printing or solution coating catalytic ink onto the surface of a proton exchange membrane. The proton exchange membrane may contain cerium oxide (CeO2) coated silica (SiO2) particles (having the same or different composition as the cerium oxide (CeO2) coated silica (SiO2) particles present in the catalytic ink), or it may not contain cerium oxide (CeO2) coated silica (SiO2) particles.

[0232] In a third embodiment, the article is a membrane electrode assembly. The membrane electrode assembly includes a membrane having first and second surfaces, a first electrocatalytic layer adhered to the first surface, and a second electrocatalytic layer adhered to the second surface, wherein at least one of the membrane, the first or the second electrocatalytic layer comprises at least one fluorinated polymer containing a -SO2X functional group as defined above, and cerium oxide (CeO2) coated silica (SiO2) particles. When cerium oxide (CeO2) coated silica (SiO2) particles are present in more than one component of the membrane electrode assembly, they may be the same or different.

[0233] Finally, the object of the present invention is a fuel cell or electrolyzer comprising articles as defined above.

[0234] All definitions previously defined in the context of cerium oxide (CeO2) coated silica (SiO2) particles or methods for their preparation are preferably applicable to compositions comprising cerium oxide (CeO2) coated silica (SiO2) particles and fluoropolymer compositions, as well as any articles containing said compositions.

[0235] The invention will now be described in more detail with reference to the following examples, which are illustrative in nature only and are not intended to limit the scope of the invention.

[0236] Example

[0237] Characterization

[0238] Ce content via ICP-OES

[0239] Inductively coupled plasma optical emission spectrometry (ICP-OES) was used to perform mineralization on cerium oxide samples prepared by dissolving cerium oxide in a mixture of nitric acid and hydrochloric acid.

[0240] Optical emission spectroscopy was used to detect and quantify ionized elements, with wavelengths of 418.660 nm and 446.021 nm used for Ce, and wavelengths of 180.672 nm and 181.975 nm used for S.

[0241] Specific surface area of ​​particles using the BET method

[0242] The specific surface area of ​​particles was measured according to the Brunauer-Emet-Teller (BET) method described in "The Journal of the American Chemical Society", Vol. 60, p. 309, February 1938.

[0243] Crystallite size by XRD

[0244] Using a Cu X-ray tube (Cu Kα wavelength is...) XRD diffraction patterns of the powder were obtained using a Malvern panalytical XRD goniometer with Bragg-Brentano geometry. Phase identification was performed using Highscore Plus analysis software provided by the manufacturer. The cerium dioxide crystallite size was measured using Highscore Plus analysis software based on the half-width at half-maximum (FWHM) of the main peak in the XRD patterns.

[0245] Particle size distribution by laser diffraction

[0246] Particle size distribution was obtained from the dispersion of the composition in 1-propanol by laser diffraction.

[0247] D50 It has the general meaning used in the field of particle size distribution. D n Corresponding to the following particle diameters, where, based on n% of the volume, the particles have a diameter less than D. n The diameter of D. 50 The median was defined as the size value corresponding to the 50% cumulative distribution. These parameters were determined by the volume distribution of the diameter of the particle dispersion of the solid material in solution, obtained using a Malvern Mastersizer 3000 laser diffractometer. The data were processed using the Fraunhofer optical model.

[0248] A laser diffractometer uses laser diffraction technology to measure particle size by measuring the intensity of the diffracted light as a laser beam passes through a dispersed particulate sample.

[0249] Particle grinding

[0250] The product was ground into powder using an IKA grinder for 15 seconds, and then depolymerized in a suspension of 1-propanol using an Ultraturrax stirrer.

[0251] The resulting product was further wet-milled in 1-propanol using a basket mill operating with yttrium-stabilized ZrO2 balls with a diameter of 0.1-0.2 mm.

[0252] Example 1 - Preparation of cerium oxide (CeO2) coated silica (SiO2) particles ([Ce-40]) containing 40 wt% Ce relative to the total particle weight.

[0253] In the reactor, 230g of SiO2 (supplied by Solvay) was added. 43) Dispersed in 3318g of water to obtain a suspension containing 6.5% silica by weight, and 1092.1ml of 8wt% NH3 aqueous solution was added with stirring.

[0254] Then, 683.20 g of a 2.87 mol / L Ce(NO3)3 solution in water was added to the reactor at 400 rpm over 1 hour. The resulting slurry was further stirred over a period of at least 30 minutes.

[0255] The obtained slurry was filtered and dehydrated over a Buchner funnel to obtain a solid filter cake. The pH of the filtrate was 9.2.

[0256] The obtained filter cake was then calcined in a furnace at 500°C for 3 hours.

[0257] The obtained powder has a 211m² content measured using the BET method. 2 Specific surface area per g.

[0258] For example, the size of CeO2 crystallites measured by XRD is 7.7 nm.

[0259] For example, the Ce content measured by ICP-OES is 37 wt%.

[0260] Wet milling in 1-propanol and further dilution allows for the preparation of suspensions of cerium oxide (CeO2) coated silica (SiO2) particles.

[0261] Example 2 - Preparation of cerium oxide (CeO2) coated silica (SiO2) particles ([Ce-50]) containing 50 wt% Ce relative to the total particle weight

[0262] In the reactor, 175g of SiO2 (supplied by Solvay) was added. 43) Dispersed in 2517g of water to obtain a suspension containing 6.5% silica by weight, and the pH was set to 8.5 by adding 8wt% NH3 aqueous solution.

[0263] Then, while maintaining the pH at 8.5 by adding 8 wt% NH3 aqueous solution, 853.90 g of a 2.87 mol / L Ce(NO3)3 solution in water was added to the reactor over 1 hour with stirring at 400 rpm. The resulting slurry was further stirred over a period of at least 30 minutes.

[0264] The obtained slurry is filtered and dehydrated on a Buchner funnel to obtain a solid filter cake.

[0265] The obtained filter cake was then calcined in a furnace at 500°C for 3 hours.

[0266] The obtained powder has a 166m² content measured using the BET method. 2 Specific surface area per g.

[0267] For example, the size of CeO2 crystallites measured by XRD is 5.4 nm.

[0268] For example, the Ce content, as measured by ICP-OES, is 49 wt%.

[0269] Wet milling in 1-propanol and further dilution with 1-propanol allows for the preparation of suspensions of cerium oxide (CeO2) coated silica (SiO2) particles.

[0270] Particle size distribution was obtained from the dispersion of the composition in 1-propanol by laser diffraction to obtain D 50 =0.18μm and D 90 =0.41μm.

[0271] Example 3 - Preparation of cerium oxide (CeO2) coated silica (SiO2) particles ([Ce-60]) containing 60 wt% Ce relative to the total particle weight

[0272] In the reactor, 130.6 g of SiO2 (supplied by Solvay) was added. 43) Dispersed in 1879g of water to obtain a suspension containing 6.5% silica by weight, and the pH was set to 8.5 by adding 8wt% NH3 aqueous solution.

[0273] Then, while maintaining the pH at 8.5 by adding 8 wt% NH3 aqueous solution, 1152.2 g of a 2.87 mol / L Ce(NO3)3 solution in water was added to the reactor over 1 hour with stirring at 400 rpm. The resulting slurry was further stirred over a period of at least 30 minutes.

[0274] The obtained slurry is filtered and dehydrated on a Buchner funnel to obtain a solid filter cake.

[0275] The obtained filter cake was then calcined in a furnace at 500°C for 3 hours.

[0276] The obtained powder has a 144m² content measured using the BET method. 2 Specific surface area per g.

[0277] For example, the size of CeO2 crystallites measured by XRD is 6.6 nm.

[0278] For example, the Ce content measured by ICP-OES is 57 wt%.

[0279] Wet milling in 1-propanol and further dilution in 1-propanol allows for the preparation of suspensions of cerium oxide (CeO2) coated silica (SiO2) particles.

[0280] Comparative Example 1 - Procedure for preparing mixed oxide [MO-Ce-40] scavenger particles containing 40 wt% Ce relative to the total particle weight, according to the method described in WO 2014 / 009334.

[0281] In a sealed container, SiO2, water-soluble Ce(NO3)3·6H2O and (NH4)2SO3·H2O are suspended in water.

[0282] The weight ratio of SiO2:Ce(NO3)3·6H2O:(NH4)2SO3·H2O is 200:593:62.1. The slurry is stirred at 80°C for 10 h to provide a gel. The gel thus obtained is then heat-treated under the following conditions:

[0283] - From room temperature to 150°C (1h slope, 2.5°C / min);

[0284] - At 150℃ for 2 hours;

[0285] - From 150℃ to 300℃ (1h slope, 2.5℃ / min);

[0286] -At 300℃ for 2 hours.

[0287] The powder obtained at the end of heat treatment was cooled to room temperature and then washed with 0.5 M H₂SO₄ solution at 70 °C until ICP-OES analysis of the sample confirmed that the amounts of metallic M and sulfur remained unchanged. The powder was dried under vacuum at 80 °C for 2 h and then ground in a planetary ball mill at 200 rpm for 2 h.

[0288] The characteristics of the cerium oxide (CeO2) coated silica (SiO2) particles [Ce-40], [Ce-50] and [Ce-60] prepared in Examples 1 to 3, as well as the mixed oxide [MO-Ce-40] scavenger particles prepared in Comparative Example 1, are reported in Table 1 below.

[0289] Table 1

[0290]

[0291] Example 4 - Preparation of fluorinated polymers (P1) containing -SO3H functional groups

[0292] The following reagents were placed in a 22L autoclave:

[0293] 11.5L of demineralized water;

[0294] 980g of monomers have the following formula: CF2=CF-O-CF2CF2-SO2F

[0295] 3100g of 5% by weight CF2ClO(CF2CF(CF3)O) n (CF2O) m A solution of CF2COOK (average molecular weight = 521, ratio n / m = 10) in water.

[0296] The autoclave, stirred at 470 rpm, was heated to 60°C. A water-based solution containing 6 g / L potassium persulfate was added in 150 mL. The pressure was maintained at 12 bar (abs) by feeding tetrafluoroethylene.

[0297] After adding 1200g of tetrafluoroethylene to the reactor, 220g of monomer CF2=CF-O-CF2CF2-SO2F is added for every 200g of tetrafluoroethylene fed into the autoclave.

[0298] The reaction was stopped after 280 minutes by stopping stirring, the autoclave was cooled and the internal pressure was reduced by venting the tetrafluoroethylene; a total of 4000g of tetrafluoroethylene was fed.

[0299] The latex was then coagulated by freezing and thawing, and the recovered polymer was washed with water and dried at 150°C for 24 hours. The polymer was then treated with fluorine gas at 80°C for 8 hours in a metal container, followed by purging with nitrogen gas for several hours to remove any residual unstable end groups.

[0300] The polymer thus obtained was impregnated in a KOH solution (10% by weight) at 80°C for 8 hours, followed by washing in demineralized water at room temperature. It was then impregnated in an HNO3 solution (20% by weight) at room temperature for 2 hours, followed by washing in demineralized water at room temperature to convert all functional groups to -SO3H functional groups.

[0301] The resulting fluorinated polymer (P1) in the form of -SO3H was then dried in a vacuum oven at 80°C. The equivalent weight of the polymer (EW) was determined to be 790 g / eq (by IR analysis of the precursor polymer).

[0302] Example 5 - A suspension comprising cerium oxide (CeO2)-coated silica (SiO2) particles prepared in Example 2 dispersed in 1-propanol and mixed oxide scavenger particles prepared as in Comparative Example 1.

[0303] A suspension of cerium oxide (CeO2)-coated silica (SiO2) particles [Ce-50] prepared in Example 2, comprising 15 wt% of the total weight of the suspension, in 1-propanol was sonicated for 2 h to obtain a complete dispersion of the solids. The solid content in the dispersion was determined using a thermobalance (160 °C, 45 min).

[0304] Similarly, a suspension in 1-propanol containing 15 wt% of the [Mo-Ce-40] mixed oxide scavenger of Comparative Example 1 relative to the total weight of the suspension was prepared.

[0305] Example 6 - A liquid composition comprising a suspension of (CeO2)-coated silica (SiO2) particles prepared in P1 and Example 5, or a suspension of mixed oxide scavenger particles prepared as in Comparative Example 1.

[0306] The suspension of cerium oxide (CeO2) coated silica (SiO2) particles [Ce-50] obtained in Example 5 was added to an aqueous dispersion of P1 (20 g), which further contained 1-propanol (7.5 g), DMSO2 (1.6 g), and H2O (3 g). The mixture was stirred at room temperature to homogenize the dispersion.

[0307] The amounts of cerium oxide (CeO2) coated silica (SiO2) particles [Ce-50] and P1 added during the preparation of the liquid composition were calculated to obtain the final cerium content in the composition based on fluorinated polymer P1 0.7% ± 0.1% w / w.

[0308] Liquid compositions were prepared in a similar manner from a suspension of mixed oxide scavenger particles, as prepared in Comparative Example 1.

[0309] Example 7 - Membrane Preparation - General Procedure

[0310] The mixture from Example 6 was cast onto a glass substrate with a wet thickness of 500 μm using a doctor blade technique, and then dried in a ventilated oven at 60°C for 1 hour, increasing the temperature from 60°C to 90°C over 1 hour, and then decreasing the temperature from 90°C to 190°C over 1 hour. The resulting film thickness was 50 ± 5 μm.

[0311] The amount of Ce element in the membrane containing [Ce-50], as measured by ICP-OES, is 0.7% ± 0.1% w / wt relative to the total weight of the membrane (M2).

[0312] The amount of Ce element in the membrane containing [MO-Ce-40], as measured by ICP-OES, is 0.8% ± 0.1% w / wt relative to the total weight of the membrane (M3).

[0313] Characterization of fuel cells using membranes prepared in Examples 8-7

[0314] The membrane obtained as described in Example 7 was assembled on an effective area of ​​50 cm². 2 The membrane was placed in a custom stacking fixture and tested on a Greenlight Innovation G100 test bench. A gas diffusion layer coated with a self-made catalyst (approximately 0.35 mg / cm³) was then applied. 2 Pt) are assembled together.

[0315] These membranes were tested under the following operating conditions:

[0316] - Anode side flow: 250 nccm pure H2, 61°C dew point, 1 bar (ABS)

[0317] - Cathode side flow: 250 nccm pure O2, 61°C dew point, 1 bar (ABS)

[0318] - Battery temperature: 90℃.

[0319] The voltage was monitored during the test. The test ended at a voltage below 0.7V, which was typically assumed to indicate the formation of a pore in the film. The results are reported in Table 2.

[0320] Table 2

[0321]

[0322] Compared to a membrane containing only fluorinated polymer (P1) (reference membrane (M1)), a membrane (M2) containing cerium oxide-coated silica particles of the present invention exhibits a significant increase in stability under fuel cell operating conditions. In fact, in the case of membrane (M2), the time to reach a voltage below 0.7V is 660 hours.

[0323] Furthermore, compared to the membrane (M3) containing the mixed oxide scavenger prepared according to the method described in WO 2014 / 009334 in Comparative Example 1, the membrane (M2) containing the cerium oxide-coated silica particles of the present invention exhibits a significant increase in stability under fuel cell operating conditions. In fact, in the case of membrane (M2), the time to reach a voltage below 0.7V is 660 hours, while in the case of membrane (M3) it is only 275 hours.

[0324] Therefore, silica (SiO2) particles coated with cerium oxide (CeO2) according to the present invention are superior to prior art free radical scavenger particles obtained by different methods, and are considered to be more stable in leaching during the operation of fuel cells or electrolyzers for a longer period of time.

[0325] Example 9 - The stability of cerium oxide (CeO2) coated silica (SiO2) particles ([Ce-50]) containing 50 wt% Ce element relative to the total particle weight for Ce leaching in an acidic medium was determined following the preparation scheme of Example 2, except that the filter cake was calcined at a temperature of 700 °C.

[0326] The obtained powder has a 122m² content measured using the BET method. 2 Specific surface area per g. For example, the size of CeO2 crystallites, measured by XRD, is 7.3 nm.

[0327] 2 g of the calcined product was dispersed in 100 mL of 1 M H₂SO₄. The suspension was heated at 80 °C for 24 hours (Step 1). After 24 hours, the suspension was centrifuged (9600 rpm for 15 min - Sigma 6 16KS refrigerated benchtop centrifuge, rotor Sigma 12269). The resulting solid was redispersed in 100 mL of 1 M H₂SO₄ and heated at 80 °C for 24 hours (Step 1).

[0328] The amount of Ce leached was determined by ICP-OES analysis of the two supernatants. The results in Table 3 show very low levels of leaching under acidic conditions.

[0329] Table 3

[0330] %Ce leached in step 1 %Ce leached in step 2 %Ce-total leaching 7.6 6.1 13.7

Claims

1. A cerium oxide (CeO2) coated silica (SiO2) particle, optionally containing an inorganic -SO2O2Z functional group, wherein Z is selected from the group consisting of H, alkali metals and NH4; containing 10 wt% to 70 wt% Ce element relative to the total particle weight; exhibiting a range of 80 μm as measured by the BET method. 2 / g to 220m 2 Specific surface area / g; comprising CeO2 microcrystals with dimensions ranging from 5.0 nm to 10.0 nm as measured by XRD.

2. The particles according to claim 1, characterized by the following particle size distribution: D based on volume 50 Less than 0.20 μm, preferably D 50 The particle size is less than 0.18 μm, and this distribution was obtained by laser diffraction from the dispersion of the particles in 1-propanol.

3. The particles according to claim 1 or 2, wherein, Based on volume D 90 Less than 0.50 μm, preferably D 90 Less than 0.45 μm, more preferably D 90 The particle size is less than 0.42 μm, and this distribution was obtained by laser diffraction from the dispersion of the particles in 1-propanol.

4. A liquid composition (LC1) comprising particles according to claims 1 to 3 dispersed in a liquid medium (L1).

5. A method (method A) for preparing cerium oxide (CeO2) coated silica (SiO2) particles according to any one of claims 1 to 3, the method comprising the following steps: a) Provide an aqueous suspension containing SiO2, wherein the pH of the suspension is set between 8 and 9 by adding an aqueous ammonia (NH3) solution; b) While maintaining the pH value between 8 and 9 by adding an ammonia solution, an aqueous solution of Ce(NO3)3 is added to the suspension under stirring to obtain a slurry containing cerium hydroxide precipitated on SiO2. c) Filter the slurry obtained in step b) to recover cerium hydroxide precipitated onto SiO2 in solid form; d) The solid obtained in step c) is calcined in an oxidizing atmosphere at a temperature ranging from 250°C to 800°C for a duration ranging from 1 to 10 hours to obtain cerium oxide (CeO2) coated silicon dioxide (SiO2) in particulate form. e) Optionally mill the recovered particles from step d) to obtain the desired particle size.

6. A method (method A') for preparing cerium oxide (CeO2) coated silica (SiO2) particles according to any one of claims 1 to 3, the method comprising the following steps: a') Provide an ammonia solution (E) with a pH value set between 7 and 11; b') While maintaining the pH value between 7 and 11 by adding an aqueous ammonia solution (E'), an aqueous suspension (S2) containing SiO2 suspended in an aqueous Ce(NO3)3 solution is added to the aqueous solution (E) under stirring to obtain a slurry containing cerium hydroxide precipitated on SiO2. c') The slurry obtained in filtration step b') is used to recover cerium hydroxide precipitated onto SiO2 in solid form; d') The solid obtained in step c') is calcined in an oxidizing atmosphere at a temperature ranging from 250°C to 800°C for a duration ranging from 1 to 10 hours to obtain cerium oxide (CeO2) coated silicon dioxide (SiO2) in particulate form. e') Optionally, the recovered particles from step d') are milled to obtain the desired particle size.

7. A method (Method B) for preparing cerium oxide (CeO2) coated silica (SiO2) particles according to any one of claims 1 to 3, the method comprising the following steps: a”) provides an aqueous suspension comprising SiO2, ammonia (NH3) and optionally at least one inorganic group –SO2X source; b”) Add an amount of Ce(NO3)3 aqueous solution to the suspension under stirring, such that the molar ratio of NH3 to Ce provided in step a”) is in the range of 2 to 4, to obtain a slurry containing cerium hydroxide precipitated on SiO2. c”) Filter the slurry obtained in step b”) to recover cerium hydroxide Ce(OH)3 precipitated on SiO2 in solid form; d”) The solid obtained in step c”) is calcined in an oxidizing atmosphere at a temperature ranging from 250°C to 800°C for a duration ranging from 1 to 10 hours to obtain cerium oxide (CeO2) coated silicon dioxide (SiO2) in particulate form. e”) optionally grinds the recovered particles in step d”) to obtain the desired particle size.

8. A composition (C) comprising at least one polymer containing a -SO2X functional group—wherein X is selected from X' or OZ and wherein X' is selected from the group consisting of F, Cl, Br, and I and Z is selected from the group consisting of H, alkali metals, and NH4—and cerium oxide (CeO2) coated silica (SiO2) particles according to any one of claims 1 to 3.

9. The composition (C) according to claim 8, wherein, The cerium oxide (CeO2) coated silica (SiO2) particles are present in an amount of at least 0.1 wt% and not more than 20.0 wt% relative to the weight of the polymer.

10. The composition (C) according to claim 8 or 9, wherein, The polymer containing the –SO2X functional group is a fluorinated polymer.

11. A liquid composition (LC) comprising the composition (C) according to claims 8 to 10 dispersed in a liquid medium (L).

12. The liquid composition (LC) according to claim 11, wherein, In this polymer, X = OZ and Z = H.

13. A method for preparing a composition according to any one of claims 8 to 12, the method comprising blending, in solid form or in a liquid medium (L), cerium oxide (CeO2) coated silica (SiO2) particles according to any one of claims 1 to 3 with the at least one polymer containing a –SO2X functional group.

14. An article comprising the composition according to any one of claims 8 to 10.

15. The article of claim 14, wherein it is a proton exchange membrane, an electrocatalytic layer, or a membrane electrode assembly.

16. A method for preparing an article according to claim 14 or 15, the method comprising impregnating, casting, or coating with a liquid composition (LC) according to claim 11 or 12.

17. A fuel cell or electrolyzer comprising the article of claim 14 or 15.

Citation Information

Patent Citations

  • Polymerization process of sulphonic monomers

    EP1172382A2

  • Polymerization process of sulphonic monomers

    EP1323751A2

  • Solid polymer fuel cell

    EP1662595A1

  • Reduced degradation of ion-exchange membranes in electrochemical fuel cells

    EP1702378A1

  • Heating medium carrier and manufacture thereof

    JP1998230162A

Cited By

  • High-temperature printing ink for automobile protective cover and production process of high-temperature printing ink

    CN121450152A

  • High temperature ink for automobile protective cover and production process thereof

    CN121450152B